Long-term survival in patients with septic acute kidney injury is strongly influenced by renal recovery. - Marco Fiorentino; Fadi A Tohme; Shu Wang; Raghavan Murugan; Derek C Angus; John A Kellum (PLoS ONE, 2018)
Background Several studies have shown that long-term survival after acute kidney injury (AKI) is reduced even if there is clinical recovery. However, we recently reported that in septic shock patients those that recover from AKI have survival similar to patients without AKI. Here, we studied a cohort with less severe sepsis to examine the effects of AKI on longer-term survival as a function of recovery by discharge. Methods We analyzed patients with community-acquired pneumonia from the Genetic and Inflammatory Markers of Sepsis (GenIMS) cohort. We included patients who developed AKI (KDIGO stages 2-3) and defined renal recovery as alive at hospital discharge with return of SCr to within 150% of baseline without dialysis. Our primary outcome was survival up to 3 years analyzed using Gray's model. Results Of the 1742 patients who survived to hospital discharge, stage 2-3 AKI occurred in 262 (15%), of which 111 (42.4%) recovered. Compared to recovered patients, patients without recovery were older (75 ±14 vs 69 ±15 years, p<0.001) and were more likely to have at least stage 1 AKI on day 1 (83% vs 52%, p<0.001). Overall, 445 patients (25.5%) died during follow-up, 23.4% (347/1480) for no AKI, 28% (31/111) for AKI with recovery and 44.3% (67/151) for AKI without recovery. Patients who did not recover had worse survival compared to no AKI (HR range 1.05-2.46, p = 0.01), while recovering patients had similar survival compared to no AKI (HR 1.01, 95%CI 0.69-1.47, p = 0.96). Absence of AKI on day 1, no in-hospital renal replacement therapy (RRT), higher Apache III score and higher baseline SCr were associated with recovery after AKI. Conclusions In patients with sepsis, recovery by hospital discharge is associated with long-term survival similar to patients without AKI.